4(2b-3x)=7b+5x

Simple and best practice solution for 4(2b-3x)=7b+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2b-3x)=7b+5x equation:


Simplifying
4(2b + -3x) = 7b + 5x
(2b * 4 + -3x * 4) = 7b + 5x
(8b + -12x) = 7b + 5x

Solving
8b + -12x = 7b + 5x

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-7b' to each side of the equation.
8b + -7b + -12x = 7b + -7b + 5x

Combine like terms: 8b + -7b = 1b
1b + -12x = 7b + -7b + 5x

Combine like terms: 7b + -7b = 0
1b + -12x = 0 + 5x
1b + -12x = 5x

Add '12x' to each side of the equation.
1b + -12x + 12x = 5x + 12x

Combine like terms: -12x + 12x = 0
1b + 0 = 5x + 12x
1b = 5x + 12x

Combine like terms: 5x + 12x = 17x
1b = 17x

Divide each side by '1'.
b = 17x

Simplifying
b = 17x

See similar equations:

| 8+5x-35x=8-4x+32 | | 8x-17b=7x | | n=2/4*7/8 | | 7+3x=-5x+13 | | 12x-(x+3)=30 | | 4(2x-3b)=7x+5b | | 12x-(x+3)=4 | | 2x-3+4x+1=0 | | l-100=253 | | 9y-9=6y+6 | | 18x^2+3-53x=0 | | -3z+8=-12+2z | | 4y=70+5x | | h=7*6/7 | | F(x)=3x^2-5x-50 | | 5p-1=2+20 | | -0.9m-9.5-6.46=-7+0.5m | | 4-y=29 | | 133+2x=360 | | .6+2.8+(x*.1)=4 | | 0.4s=-8.7-0.2s | | 8z-3-z=-3+7z-2 | | -18.03-2.8k=14.17+6.4k | | 13.8g-1.03=17.61+17.2g+0.74 | | 25-11=2(x-3) | | F(x)=2x^2-10x-72 | | x+21+4x=-10-4x-14 | | -8c=17.85-5.9c | | 20-14= | | F(x)=6x+10 | | 5y-5=3y+1 | | 4x-0.04x^3=0 |

Equations solver categories